Active Surveillance of Patients Colonized with CRE: A Single-Center Study Based on a Combined Molecular/Culture Protocol - Beatrice Silvia Orena; Maria Francesca Liporace; Antonio Teri; Daniela Girelli; Federica Salari; Michela Mutti; Gabriele Giordano; Claudia Alteri; Flaminia Gentiloni Silverj; Caterina Matinato; Annapaola Callegaro; Lisa Cariani (Antibiotics)
Background/Objectives: Carbapenem-resistant Enterobacteriaceae (CRE) are types of bacteria that need urgent attention globally. Active surveillance programs at hospitals are essential for the early identification of CRE carriers and the timely adoption of infection control measures. We aimed to analyze the epidemiology of CRE identified by multiplex RT-PCR in rectal swabs of patients upon admission to high-risk wards and to compare data obtained from both molecular and culture CRE screening. Methods: A total of 2861 rectal swabs, prospectively collected within 12–24 h of admission, underwent molecular screening for identification of K. pneumoniae carbapenemase (KPC), New Delhi metallo-β-lactamase (NDM), Verona integron-mediated metallo-β-lactamase (VIM), imipenemase (IMP), and OXA-48 (AllplexTM Entero-DR Assay). Only samples that tested positive or invalid underwent culture testing (Agar MacConkey and CHROMID® CARBA plates, bioMérieux, Craponne, France). Results: A total of 118 out of 2861 (about 4%) were positive for at least one carbapenem-resistant gene by a molecular approach (MA), with KPC, NDM, and VIM having the highest prevalence. Culture testing confirmed the presence of carbapenemase in 89 samples (75.4%), showing a disagreement rate of about 25% between the two methods, which, unfortunately, rises up to 60% for VIM. The dominant bacterial species were K. pneumoniae and E. coli (MALDI-TOF mass spectrometry). Conclusions: Our data underlined the need for the molecular screening of CRE carriers in order to implement active surveillance protocol in critical care settings and to improve infection control measures.